Effect of alkali cation type on the plasticizing effect of ligno-sulfonate in alkali-activated systems. Issue 1 (November 2021) - Iliushchenko, V; Bilek Jr., V; Kalina, L; Hruby, P; Opravil, T; Bojanovsky, J
Abstract: The rheological properties of alkali-activated systems are significantly affected by the nature of the alkaline activator. Hydroxide-activated systems' workability is typically lower than that of alkali-activated systems but can be improved by lignosulfonate plasticizer. However, the lignosulfonate plasticizer's effectivity depends on the dosage of lignosulfonate, the nature of hydroxide and pH of their solutions. Therefore, in this study, the effectiveness of lignosulfonate plasticizer with respect to alkali ion type (Na+, K+, Li+) in alkali hydroxide-activated systems based on ground granulated blast furnace slag was evaluated. The concentration of the alkaline activator (NaOH, KOH and LiOH) was the same in all cases of 4M. The superplasticizer dosage was 0%, 0.5% and 1.0% of dry matter of lignosulfonate plasticizer to the slag weight. Rheological properties were determined using a rotational rheometer equipped with vane in-cup geometry working in oscillation amplitude sweep mode, from which critical strain and corresponding viscoelastic variables were obtained.